Business practices in the marble activity in Huila - Andrade Navia , Juan Manuel (Universidad Francisco de Paula Santander, 2015)
The evolution of economic activities, driven by entrepreneurial agents, is an object of study to understand in all its expression, the current reality of the regions. It is in this logic that this study seeks to identify and understand the characteristics of the origin of the marble activity in the department of Huila and the practices of its entrepreneurial agents. Consequently, for the purpose of a better understanding, the activity was classified into two levels of management; the extractive activity and the transforming activity, except in some cases where both forms are present under the control of the same agent. Likewise, it can be deduced that the experience accumulated by the agents plays a determining role in the realization of entrepreneurial initiatives in the activity. On the other hand, it can be seen that during the 1950s and 1960s, the State stimulated the activity by financing studies to determine the potential of the mineral resource. However, after 1990, its role was limited to controlling de facto or traditional mining, with little effort to develop it. In this sense, there was little support, especially from entities such as SENA and the municipalities.